Dielectric composition, dielectric element, and stacked electronic component
The dielectric composition, featuring a tungsten bronze-type crystal structure and a perovskite-type crystal structure with optimized sodium and strontium concentrations, addresses the issue of relative permittivity stability under high electric fields and high DC voltage, achieving high performance and minimal reduction in relative permittivity.
Patent Information
- Application Number
- JP2023178179
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-28
AI Technical Summary
Conventional dielectric compositions with a tungsten bronze structure exhibit insufficient stability in relative permittivity under high electric fields, leading to significant reduction when a high DC voltage is applied.
A dielectric composition comprising a first phase with a tungsten bronze-type crystal structure and a second phase with a perovskite-type crystal structure, where the second phase is present in a specific ratio within the observation range, optimizing the sodium and strontium concentrations between the phases.
The dielectric composition maintains a high relative permittivity under high electric fields and exhibits a minimal reduction in relative permittivity before and after the application of a high DC voltage, ensuring stability and performance in high-voltage applications.
Smart Images

Figure 2025068346000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a dielectric composition, a dielectric element, and a laminated electronic component. [Background technology]
[0002] Dielectric capacitors (e.g., multilayer ceramic capacitors) are capacitors having a dielectric layer formed of a dielectric composition, and are used as major components in various electronic devices such as home appliances and automobile control devices. Among such dielectric capacitors, for example, those used in the power trains of electric vehicles are applied with high voltages (e.g., 400V to 800V) as batteries become higher voltage, and therefore are required to maintain a high relative dielectric constant under a high electric field as well as a high withstand voltage (not breaking down under the applied high voltage). Furthermore, this type of dielectric capacitor is required to have a large electrostatic capacitance (i.e., large capacity) in addition to the high withstand voltage and high relative dielectric constant under a high electric field.
[0003] As shown in Patent Document 1, in order to obtain a large capacitance in an environment where a high voltage is applied, it is required that the change (reduction) in the relative dielectric constant when a DC voltage is applied is small.
[0004] Conventionally, BaTiO with high dielectric constant was used as a dielectric capacitor. 3 Dielectric compositions containing BaTiO 3 Dielectric compositions containing such a material have a significantly reduced relative dielectric constant under a high electric field. For this reason, it has been proposed to use a dielectric composition having a tungsten bronze structure, as shown in Patent Document 1, for example, in a dielectric capacitor. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2017 / 163845 Summary of the Invention [Problem to be solved by the invention]
[0006] In conventional dielectric compositions having a tungsten bronze type structure, although the change (reduction) in the dielectric constant is small, the dielectric constant under a high electric field is not sufficiently high, which has been a problem.
[0007] An object of the present invention is to provide a dielectric composition etc. which shows a small decrease in relative dielectric constant before and after application of a high DC voltage and has a high relative dielectric constant under a high electric field. [Means for solving the problem]
[0008] The means for solving the above problems are as follows. <1> A dielectric composition comprising a first phase having a tungsten bronze type crystal structure containing at least Sr, Na, Nb, Ca, Y, and Zr, and a second phase having a perovskite type crystal structure containing at least Sr, Na, Ca, Y, and Zr, wherein, in an observation area set on a cut surface of the dielectric composition, the second phase is contained in a proportion of 8.8% or more and 60% or less of the area (100%) of the entire observation area excluding pores.
[0009] <2> The concentration of Na contained in the second phase is 2.1 times or more and 2.5 times or less than the concentration of Na contained in the first phase, and the concentration of Sr contained in the second phase is 0.59 times or more and 0.63 times or less than the concentration of Sr contained in the first phase. <1> The dielectric composition according to claim 1 .
[0010] <3> The second phase is contained in a proportion of 8.8% to 32% of the total area (100%) of the observation range excluding pores. <1> or <2> The dielectric composition according to claim 1 .
[0011] <4> The above <1> from <3> A dielectric element comprising a dielectric ceramic formed from the dielectric composition according to any one of the above items and an electrode attached to the dielectric ceramic.
[0012] <5> The above <1> from <3> 1. A laminated electronic component having a laminate in which dielectric layers made of the dielectric composition according to any one of 1 to 8 and internal electrode layers are alternately laminated. Effect of the Invention
[0013] According to the present invention, it is possible to provide a dielectric composition or the like in which the decrease in the relative dielectric constant before and after application of a high DC voltage is small and which has a high relative dielectric constant under a high electric field. [Brief description of the drawings]
[0014] [Figure 1] A perspective view of a dielectric element [Diagram 2] Cross-section of a multilayer electronic component [Diagram 3] FIG. 13 is a SEM image of a cut surface of a measurement sample in Example 4. [Figure 4] Enlarged view of a portion of the SEM image in Figure 3 [Diagram 5] FIG. 13 is a diagram showing a first binarized image corresponding to the SEM image of Example 4. [Figure 6] FIG. 13 is a diagram showing a second binarized image corresponding to the SEM image of Example 4. [Figure 7] 1 shows X-ray diffraction patterns of Examples 4 and 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The dielectric composition, the dielectric element, and the laminated electronic component according to the embodiment will be described below.
[0016] The dielectric composition comprises a first phase having a tungsten bronze type crystal structure containing at least Sr, Na, Nb, Ca, Y, and Zr, and a second phase having a perovskite type crystal structure containing at least Sr, Na, Ca, Y, and Zr.
[0017] In the observation area set on the cut surface of the dielectric composition, the second phase is contained in a ratio of 8.8% to 60% (preferably, 8.8% to 32%) of the total area (100%) of the observation area excluding pores. The remainder of the area of the observation area excluding the second phase is the first phase.
[0018] The tungsten bronze type crystal structure in the first phase is made of a tungsten bronze type composite oxide containing at least Sr, Na, Nb, Ca, Y, and Zr. The tungsten bronze type composite oxide is represented by the following composition formula (1).
[0019] Sr a Ca b Y c Na x Nb 5-d Zr d O 15 ...(1)
[0020] The values of the coefficients x, a, b, c, and d in the above composition formula (1) are appropriately selected from values that establish a tungsten bronze type crystal structure and are preferable in terms of the electrical properties of the dielectric composition.
[0021] Specifically, the coefficient a of Sr is 1.34≦a≦1.75, the coefficient b of Ca is 0.05≦b≦0.11, the coefficient c of Y is 0.09≦c≦0.14, the coefficient x of Na is 0.82≦x≦1.04, the coefficient d of Zr is 0.02≦d≦0.08, and the coefficient 5-d of Nb is 4.82≦5-d≦4.98.
[0022] The perovskite-type crystal structure in the second phase is made of a perovskite-type complex oxide containing at least Sr, Na, Ca, Y, and Zr. The perovskite-type complex oxide is represented by the following composition formula (2).
[0023] (Sr e Ca f Y g Na h )(Nb i Zr j )O3 ...(2)
[0024] As the values of the coefficients e, f, g, h, i, and j in the above composition formula (2), values preferable from the viewpoint of the electrical properties of the dielectric composition are appropriately selected from among values that establish a perovskite type crystal structure.
[0025] Specifically, the coefficient e of Sr is 0.186≦e≦0.242, the coefficient f of Ca is 0.010≦f≦0.020, the coefficient g of Y is 0.007≦g≦0.009, and the coefficient h of Na is 0.431≦h≦0.505.
[0026] In addition, the coefficient i of Nb is 0.911≦i≦0.998, and the coefficient j of Zr is 0.009≦j≦0.089.
[0027] In the dielectric composition, the concentration of Na contained in the second phase is preferably 2.1 times or more and 2.5 times or less than the concentration of Na contained in the first phase.
[0028] In the dielectric composition, the concentration of Sr contained in the second phase is preferably 0.59 to 0.63 times the concentration of Sr contained in the first phase.
[0029] The dielectric composition may contain a crystal phase other than the first phase and the second phase as long as it does not impair the object of the present invention.
[0030] Furthermore, the dielectric composition may contain elements other than those contained in the first and second phases as inevitable impurities at a ratio of 1000 ppm or less.
[0031] Examples of raw materials used in the production of the dielectric composition include an Sr-containing compound containing strontium, an Na-containing compound containing sodium, an Nb-containing compound containing niobium, a Ca-containing compound containing calcium, an Y-containing compound containing yttrium, and a Zr-containing compound containing zirconium.
[0032] Examples of Sr-containing compounds include various inorganic powders such as Sr oxides, Sr composite oxides, Sr hydroxides, Sr carbonates, Sr chlorides, Sr sulfates, Sr nitrates, Sr phosphates, etc. Specifically, strontium carbonate powder is used.
[0033] Examples of the Na-containing compound include various inorganic powders such as oxides of Na, composite oxides of Na, hydroxides of Na, carbonates of Na, chlorides of Na, sulfates of Na, nitrates of Na, and phosphates of Na. Specifically, sodium carbonate powder is used. Specifically, sodium carbonate powder is used.
[0034] Examples of Nb-containing compounds include various inorganic powders such as Nb oxide, Nb composite oxide, Nb hydroxide, Nb carbonate, Nb chloride, Nb sulfate, Nb nitrate, Nb phosphate, etc. Specifically, niobium oxide powder can be used.
[0035] Examples of the Ca-containing compound include various inorganic powders such as Ca oxide, Ca composite oxide, Ca hydroxide, Ca carbonate, Ca chloride, Ca sulfate, Ca nitrate, Ca phosphate, etc. Specifically, calcium carbonate powder can be used.
[0036] Examples of the Y-containing compound include various inorganic powders such as an oxide of Y, a composite oxide of Y, a hydroxide of Y, a carbonate of Y, a chloride of Y, a sulfate of Y, a nitrate of Y, and a phosphate of Y. Specifically, yttrium oxide powder can be used.
[0037] Examples of the Zr-containing compound include various inorganic powders such as Zr oxide, Zr composite oxide, Zr hydroxide, Zr carbonate, Zr chloride, Zr sulfate, Zr nitrate, Zr phosphate, etc. Specifically, zirconium oxide powder can be used.
[0038] The method for producing the dielectric composition will be explained appropriately in the explanation of the methods for producing the dielectric element and laminated electronic component described later.
[0039] When the second phase is contained in an observation area set on a cut surface of the dielectric composition at a ratio of 8.8% to 60% of the area of the entire observation area (100%) excluding pores, the relative dielectric constant under a high electric field (8 kV / mm) is 900 or more, and the rate of decrease (rate of change) of the relative dielectric constant before and after application of a high DC voltage is greater than -41%, and the decrease in the relative dielectric constant is kept small.
[0040] In the dielectric composition, the relative dielectric constant in the state where no electric field is applied (0 kV / mm) is not particularly limited as long as it does not impair the object of the present invention, but is preferably 1300 or more, more preferably 1400 or more, and even more preferably 1500 or more.
[0041] In particular, when the second phase is contained in an observation range set on a cut surface of the dielectric composition at a ratio of 8.8% or more and 32% or less with respect to the area (100%) of the entire observation range excluding pores, the relative dielectric constant under a high electric field (8 kV / mm) becomes 1000 or more, and the reduction rate (rate of change) of the relative dielectric constant before and after application of a high DC voltage becomes -35% or more, and the reduction rate of the relative dielectric constant is further suppressed to a small value.
[0042] Next, referring to Fig. 1, a dielectric element 200 including a dielectric ceramic 100 made of a dielectric composition will be described. Fig. 1 is a perspective view of the dielectric element 200. As shown in Fig. 1, the dielectric element 200 has a disk-shaped appearance and includes a disk-shaped dielectric ceramic (dielectric layer) 100 and electrodes 301, 302 attached to the upper and lower surfaces of the dielectric ceramic 100. The dielectric ceramic 100 is formed from the above-mentioned dielectric composition. The electrodes 301, 302 are made of, for example, Au.
[0043] Here, a description will be given of an example of a manufacturing method for the dielectric element 200. First, powders of strontium carbonate, sodium carbonate, niobium oxide, calcium carbonate, yttrium oxide, and zirconium oxide are prepared as raw material powders, and these powders are weighed out so as to obtain the desired composition.
[0044] The weighed raw powders are mixed with ethanol and wet-mixed in a ball mill for 15 hours or more to obtain a slurry. The obtained slurry is appropriately dried to obtain a mixed powder. The obtained mixed powder is calcined in an air atmosphere at a temperature condition of 1100°C to 1300°C for 5 to 7 hours to obtain a calcined powder.
[0045] The calcined powder thus obtained is mixed with a dispersant, a binder, and ethanol, and then pulverized and mixed to obtain a slurry. The slurry is dried and granulated, and the granulated material thus obtained is uniaxially pressed at a pressure of 20 MPa to obtain a disk-shaped pre-formed body. The disk-shaped pre-formed body is then subjected to a CIP process (cold isostatic pressing process) at a pressure of 150 MPa to obtain a molded body.
[0046] The obtained compact is held at 650°C for 4 hours to remove the binder. The compact after the binder removal process is sintered in air at a temperature of 1300 to 1350°C for 4 hours in an air atmosphere to obtain a dielectric ceramic (dielectric layer) made of a dielectric composition. Both main surfaces (upper and lower surfaces) of the obtained dielectric ceramic are polished, and then external electrodes made of Au are formed on both main surfaces by a sputtering method to obtain a dielectric element 200.
[0047] Next, a laminated electronic component 1 including a dielectric layer 11 made of a dielectric composition will be described with reference to FIG. 2. FIG. 2 is a cross-sectional view of the laminated electronic component 1. The laminated electronic component 1 is a so-called laminated ceramic capacitor, and as shown in FIG. 2, includes a laminate 10 having a plurality of dielectric layers 11 formed of a dielectric composition, first internal electrode layers (one example of internal electrode layers) 12 and second internal electrode layers (one example of internal electrode layers) 13 alternately laminated with the dielectric layers 11 interposed therebetween, and a first external electrode 14 and a second external electrode 15 electrically connected to the first internal electrode layers 12 and the second internal electrode layers 13 and formed on the outer surface of the laminate 10. On one side of the laminated electronic component 1, the first internal electrode layer 12 and the first external electrode 14 are connected, and on the other opposing side, the second internal electrode layer 13 and the second external electrode 15 are connected.
[0048] Examples of materials constituting the first internal electrode layer 12 and the second internal electrode layer 13 include Cu, Ag, Ni, etc. Examples of materials constituting the first external electrode 14 and the second external electrode 15 include Au, etc.
[0049] Here, a description will be given of an example of a method for manufacturing the laminated electronic component 1. First, powders of strontium carbonate, sodium carbonate, niobium oxide, calcium carbonate, yttrium oxide, and zirconium oxide are prepared as raw material powders, and these powders are weighed out so as to obtain a target composition.
[0050] The weighed raw powders are mixed with ethanol and wet-mixed in a ball mill for 15 hours or more to obtain a slurry. The obtained slurry is appropriately dried to obtain a mixed powder. The obtained mixed powder is calcined in an air atmosphere at a temperature condition of 1100°C to 1300°C for 5 to 7 hours to obtain a calcined powder.
[0051] A dispersant, a binder and ethanol are added to the calcined powder, which is then pulverized and mixed to obtain a slurry, which is then processed into a sheet shape by a doctor blade method to produce a plurality of ceramic green sheets.
[0052] Next, the electrode layers that will become the internal electrode layers (first internal electrode layer, second internal electrode layer) are formed on one side of the ceramic green sheet by, for example, screen printing using the conductive paste for the internal electrodes. The electrode layers are mainly composed of a base metal, for example, nickel (Ni).
[0053] Then, the ceramic green sheets on which the electrode layers are formed are stacked so that the electrode layers are exposed alternately from both sides, and ceramic green sheets on which no electrode layers are formed are further stacked on both sides of the obtained laminate. The obtained laminate is pressed to obtain a laminate in which the ceramic green sheets and the electrode layers are alternately stacked. The laminate is cut into a desired shape, and then subjected to a binder removal treatment by, for example, maintaining the laminate at a temperature condition of 200 to 400°C for 2 to 10 hours.
[0054] The laminate after the binder removal process is subjected to air firing by being held in an air atmosphere at a temperature condition of 1300 to 1350° C. for 4 hours. After firing, the ceramic green sheets become the dielectric layers 11, and the electrode layers become the internal electrode layers (first internal electrode layer, second internal electrode layer).
[0055] After the fired laminate 10 has its side surfaces polished (barrel polishing, sandblasting, etc.), a pair of external electrodes (first external electrode 14, second external electrode 15) made of Au are formed, for example, by sputtering on the side surfaces of the laminate 10. In this manner, the laminated electronic component 1 is obtained.
[0056] The dielectric composition disclosed in the present specification exhibits a small decrease in relative dielectric constant before and after application of a high DC voltage, and has a high relative dielectric constant under a high electric field.
[0057] Dielectric elements and laminated electronic components having a dielectric layer formed from the dielectric composition are used, for example, in the power train of an electric vehicle to which a high voltage (e.g., 400 V to 800 V) is applied. Examples of the laminated electronic components include dielectric capacitors and laminated ceramic capacitors. The dielectric composition may also be used in various electronic devices such as home appliances and automobile control devices. EXAMPLES
[0058] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples in any way.
[0059] [Examples 1 to 6, Comparative Examples 1 to 4] As raw material powders, powders of strontium carbonate, calcium carbonate, sodium carbonate, potassium carbonate, niobium oxide, yttrium oxide, and zirconium oxide were prepared, and the necessary powders were selected from among them and weighed to obtain the compositions shown in Table 1. Ethanol was added to the weighed raw material powders, and the mixture was wet-mixed in a ball mill for 15 hours or more to obtain a slurry. The obtained slurry was appropriately dried to obtain a mixed powder. The obtained mixed powder was calcined in an air atmosphere at a temperature condition of 1200°C for 6 hours to obtain a calcined powder.
[0060] The calcined powder thus obtained was mixed with a dispersant, a binder, and ethanol, and then pulverized and mixed to obtain a slurry. The slurry was dried and granulated, and the granulated material thus obtained was uniaxially pressed at a pressure of 20 MPa to obtain a disk-shaped pre-formed body. The disk-shaped pre-formed body was then subjected to a CIP process (cold isostatic pressing process) at a pressure of 150 MPa to obtain a molded body.
[0061] The obtained molded body was held at 650°C for 4 hours to carry out a binder removal treatment. The molded body after the binder removal treatment was sintered in air by holding it in an air atmosphere at a temperature condition of 1300 to 1350°C for 4 hours to obtain a dielectric ceramic made of a dielectric composition. Both main surfaces (upper and lower surfaces) of the obtained dielectric ceramic were polished to obtain a measurement sample including both mirror-like main surfaces.
[0062] Thereafter, in order to evaluate the electrical characteristics, external electrodes made of Au were formed on both main surfaces of the dielectric ceramic by a sputtering method, thereby obtaining a dielectric element (a measurement sample for evaluating electrical characteristics).
[0063] 〔evaluation〕 For each of the samples of Examples 1 to 6 and Comparative Examples 1 to 4, the following tests were carried out.
[0064] (Dielectric constant) The relative dielectric constants (0 kV / mm, 8 kV / mm) of the measurement samples for evaluating electrical properties were calculated from the capacitance values at 1 kHz measured using an impedance analyzer at room temperature with no DC voltage applied (i.e., 0 kV / mm) and the capacitance values at 1 kHz measured using an impedance analyzer at room temperature with a DC voltage of 8 kV / mm applied. The results are shown in Table 3.
[0065] (Reduction rate of dielectric constant) The rate of decrease (rate of change) [%] from the dielectric constant at an applied voltage of 0 kV / mm to the dielectric constant at an applied voltage of 8 kV / mm was calculated by [(dielectric constant at 8 kV / mm) - (dielectric constant at 0 kV / mm)] / (dielectric constant at 0 kV / mm) x 100. The results are shown in Table 3.
[0066] (Phase II ratio) Apart from the measurement sample for evaluating electrical properties, a measurement sample without external electrodes was prepared and cut in the thickness direction. The cut surface was polished. The cut surface of the polished measurement sample was photographed at 500x magnification using a scanning electron microscope (SEM) to obtain an SEM image of the cut surface. The SEM image was analyzed using image processing software (Image-J) to calculate the proportion of subphases in the entire observation range S (excluding pores) set on the cut surface (a rectangular range of 1280 pixels vertically and 960 pixels horizontally) by the following procedure.
[0067] Here, an example of the SEM image is shown in Fig. 3 and Fig. 4. Fig. 3 is an SEM image of a cut surface of the measurement sample (dielectric composition 2) of Example 4, and Fig. 4 is an enlarged view of a part of the SEM image of Fig. 3. In Fig. 3 and Fig. 4, the black dotted parts correspond to the pores (voids) 20 formed in the dielectric composition 2. In Fig. 3 and Fig. 4, the lightest colored parts correspond to the first phase 21 in the dielectric composition. In Fig. 3 and Fig. 4, the parts that are darker than the first phase 21 and lighter than the pores 20 (i.e., gray parts) correspond to the second phase 22 in the dielectric composition. In this way, in the SEM image of the measurement sample, the first phase, the second phase, and the pores can be distinguished from each other by the difference in color (such as the density of pixel color).
[0068] Therefore, by setting appropriate thresholds for the SEM images, a binarization process for detecting the second phase and pores (hereinafter referred to as the "first binarization process") and a binarization process for detecting only the pores (hereinafter referred to as the "second binarization process") were performed.
[0069] Next, based on the first binarized image obtained by the first binarization process, the ratio of the total area of the second phase and pores to the total area of the observation range of the SEM image (hereinafter referred to as "ratio A1") was calculated by the Li method. For reference, FIG. 5 shows the first binarized image corresponding to the SEM image of Example 4. In FIG. 5, the black spot-like parts 23 correspond to the second phase and / or pores.
[0070] In addition, based on the second binarized image obtained by the second binarization process, the ratio of the pore area to the entire observation range of the SEM image (hereinafter referred to as "ratio A2") was calculated by the IsoDATA method. For reference, FIG. 6 shows a second binarized image corresponding to the SEM image of Example 4. In FIG. 6, the black spot-like parts 24 correspond to the pores.
[0071] Then, based on the obtained ratios A1 and A2, the ratio of the area of the second phase to the total area of the observation range of the cut surface excluding the pores was calculated using the formula [((Ratio A1)-(Ratio A2)) / (1-(Ratio A2))×100]. The results are shown in Table 3.
[0072] (Elemental analysis) The cut surface of the measurement sample was subjected to elemental analysis of the first and second phases using an electron probe microanalyzer (EPMA). The results are shown in Table 1. The measurement conditions were an acceleration voltage of 15 kV and a probe current of 25 nA. Table 1 also shows the concentration (mol%) of each element relative to 100 mol% of all elements.
[0073] For reference, the composition formula representing the tungsten bronze crystal structure of the first phase and the composition formula representing the perovskite crystal structure of the second phase in each example are shown in Table 2, which were determined from the results of elemental analysis (element ratios) in Table 1. The composition formula of the tungsten bronze crystal structure was determined so that the sum of the Nb concentration and the Zr concentration shown in Table 1 (Nb+Zr) was 5 (the coefficients of Nb and Zr in the composition formula). The composition formula of the perovskite crystal structure was determined so that the sum of the Nb concentration and the Zr concentration shown in Table 1 (Nb+Zr) was 1 (the coefficients of Nb and Zr in the composition formula).
[0074] (Sr concentration ratio) Based on the above-mentioned EPMA measurement results (see Table 1), the ratio of the concentration of Sr contained in the second phase to the concentration of Sr contained in the first phase of the measurement sample (Sr concentration ratio) was calculated. The results are shown in Table 3.
[0075] (Na concentration ratio) Based on the above-mentioned EPMA measurement results (see Table 1), the ratio of the Na concentration in the second phase to the Na concentration in the first phase of the measurement sample (Na concentration ratio) was calculated. The results are shown in Table 3.
[0076] (XRD) The polished surface of the measurement sample was subjected to structural analysis by XRD (X-ray diffraction method). A micro X-ray diffractometer was used as the XRD measuring device, and analysis was performed in the range of 2θ = 20° to 90° using CuKα radiation.
[0077] For reference, Fig. 7 shows the X-ray diffraction patterns of Examples 4 and 5. Of the graphs shown above and below in Fig. 7, the upper graph is the X-ray diffraction pattern of the measurement sample of Example 4, and the lower graph is the X-ray diffraction pattern of the measurement sample of Example 5. The horizontal axis of Fig. 7 represents the diffraction angle (°), and the vertical axis represents the intensity (arbitrary unit).
[0078] [Table 1]
[0079] [Table 2]
[0080] [Table 3]
[0081] In the case of the dielectric compositions of Examples 1 to 6, the results of XRD and EPMA confirmed that the first phase had a tungsten bronze type crystal structure containing Sr, Na, Nb, Ca, Y, and Zr, and the second phase had a perovskite type crystal structure containing Sr, Na, Ca, Y, and Zr.
[0082] In contrast, in the case of the dielectric composition of Comparative Example 1, the results of XRD and EPMA confirmed that it consisted only of a first phase (tungsten bronze-type complex oxide) having a tungsten bronze-type crystal structure containing Sr, Na, Nb, Ca, Y, and Zr.
[0083] In addition, in the case of the dielectric compositions of Comparative Examples 2 to 4, the results of XRD and EPMA confirmed that they consisted only of a first phase having a tungsten bronze type crystal structure containing Sr, Na, Nb, K, Ca, Y, and Zr.
[0084] In the case of Examples 1 to 6, in the observation area S set on the cut surface, the second phase was contained in a ratio of 8.8% to 60% with respect to the total area (100%) of the observation area S excluding pores (see Table 3). In contrast, the dielectric compositions of Comparative Examples 1 to 4 did not contain a second phase, and therefore the Sr concentration ratio was 0 (see Table 3).
[0085] In Examples 1 to 6, the dielectric constant under a high electric field (8 kV / mm) was 900 or more, and the rate of decrease (rate of change) in the dielectric constant before and after the application of a high DC voltage was greater than -41%, so that the decrease in the dielectric constant was kept small.
[0086] The dielectric constant of the dielectric composition of Comparative Example 1 was small under a high electric field (8 kV / mm). Moreover, the dielectric constant of the dielectric composition of Comparative Example 1 decreased more than that of Examples 1 to 6.
[0087] Furthermore, in the dielectric compositions of Comparative Examples 2 to 4, although the relative dielectric constant under a high electric field (8 kV / mm) was large, the degree of decrease in the relative dielectric constant was larger than in Examples 1 to 6.
[0088] In the dielectric compositions of Examples 1 to 6, the Na concentration in the second phase was 2.1 to 2.5 times the Na concentration in the first phase, and the Sr concentration in the second phase was 0.59 to 0.63 times the Sr concentration in the first phase.
[0089] In particular, in the case of Examples 3 to 6, in the observation area S set on the cut surface, the second phase was contained at a ratio of 8.8% to 32% with respect to the area (100%) of the entire observation area S excluding pores (see Table 3). In Examples 3 to 6, the relative dielectric constant under a high electric field (8 kV / mm) was 1000 or more, and the reduction rate (change rate) of the relative dielectric constant before and after application of a high DC voltage was -35% or more, so that the reduction in the relative dielectric constant was further suppressed to a small extent. [Explanation of symbols]
[0090] 100...dielectric ceramic (dielectric layer), 200...dielectric element, 301, 302...electrodes, 1...laminated electronic component, 10...laminated body, 11...dielectric layer, 12...first internal electrode layer (internal electrode layer), 13...second internal electrode layer (internal electrode layer), 14...first external electrode, 15...second external electrode, 2...dielectric composition, 20...pore, 21...first phase, 22...second phase
Claims
1. A first phase having a tungsten bronze type crystal structure containing at least Sr, Na, Nb, Ca, Y, and Zr; A dielectric composition comprising: a second phase having a perovskite-type crystal structure containing at least Sr, Na, Ca, Y, and Zr; A dielectric composition, wherein, in an observation area set on a cut surface of the dielectric composition, the second phase is contained in a proportion of 8.8% or more and 60% or less of the area (100%) of the entire observation area excluding pores.
2. The concentration of Na contained in the second phase is 2.1 times or more and 2.5 times or less than the concentration of Na contained in the first phase; and 2. The dielectric composition according to claim 1, wherein the concentration of Sr contained in the second phase is 0.59 to 0.63 times the concentration of Sr contained in the first phase.
3. 3. The dielectric composition according to claim 1, wherein the second phase is contained in a proportion of 8.8% or more and 32% or less with respect to the area (100%) of the entire observation range excluding pores.
4. A dielectric element comprising: a dielectric ceramic formed from the dielectric composition according to claim 1 or 2; and an electrode attached to the dielectric ceramic.
5. 3. A laminated electronic component having a laminate formed by alternately laminating dielectric layers made of the dielectric composition according to claim 1 or 2 and internal electrode layers.
Citation Information
Patent Citations
Dielectric composition, dielectric element, electronic component and laminate electronic component
WO2017163845A1